COMPARISON OF ORAL AZITHROMYCIN WITH ORAL DOXYCYCLINE IN THE TREATMENT OF ACNE VULGARIS - Ullah, Ghafoor; Noor, Sahibzada Mehmood; Bhatti, Zubair; Ahmad, Munir; Bangash, Abdur Rahim (Journal of Ayub Medical College Abbottabad, 2014)
Background: Acne vulgaris is a common inflammatory disorder of the skin that involves pilosebaceous units. This study was conducted to compare the efficacy of oral azithromycin with oral doxycycline in the treatment of acne vulgaris in our population. Methods: This randomized controlled trial was conducted in the dermatology department of Lady Reading Hospital, Peshawar from January to December 2011. All male and female patients of age (14-30 years) having moderate acne vulgaris on face only were included in the study. Patients were randomly divided into two groups. Patients in first group were given azithromycin 500 mg daily before meal for 4 consecutive days monthly for 3 months while patients in second group were given doxycycline 100 mg daily after meals for 3 months. Patients were followed up after taking treatment for three months to see the response of each drug. Response was graded as excellent, good, moderate, mild and no response. Results: A total of 386 patients equally divided in azithromycin and doxycycline groups. Male to female ratio in azithromycin and doxycycline groups was 0.82:1.11 and 0.89:1.04 respectively. Mean age in both groups was 18.45±2.91 years and 17.96±2.59 years respectively. In azithromycin group, an excellent response was noted in 6 (3.1%), and good response was observed in 44 (22.8%) patients. In doxycycline group 22 (11.4%) patients had excellent and 107 (55.4%) patients had good response. The difference being statistically significant. Conclusion: Doxycycline is a better option for treatment of acne vulgaris as compared to azithromycin. Keywords: Doxycycline, Azithromycin, Acne vulgaris